[MoS4](2-)-Intercalated NiCo-layered double hydroxide nanospikes: an efficiently synergized material for urine to direct H-2 generation - Nadeema, Ayasha; Kashyap, Varchaswal; Gururaj, Rakshitha; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2019)
Substituting the energy-uphill water oxidation half-cell with readily oxidizable urea-rich urine, a ground-breaking bridge is constructed, combining the energy-efficient hydrogen generation and environmental 6 protection. Hence, designing a robust multifunctional electrocatalyst is desirable for widespread implementation of this waste to fuel technology. In this context, here, we report a simple tuning of the electrocatalytically favorable characteristics of NiCo-layered double hydroxide by introducing [MoS4]2- in its interlayer space. The [MoS4]' insertion as well as its effect on the electronic structure tuning is thoroughly studied via X-ray photoelectron spectroscopy in combination with electrochemical analysis. This insertion induces overall electronic structure tuning of the hydroxide layer in such a way that the designed catalyst exhibited favorable kinetics toward all the required reactions of hydrogen generation. This is why our homemade catalyst, when utilized both as a cathode and anode to fabricate a urea electrolyzer, required a mere X1.37 V cell potential to generate sufficient H2 by reaching the benchmark 10 mA cm-2 in 1 M KOH/0.33 M urea along with long-lasting catalytic efficiency. Other indispensable reason of selecting [MoS4]2- is its high-valent nature making the catalyst highly selective and insensitive to common catalyst-poisoning toxins of urine. This is experimentally supported by performing the real urine electrolysis, where the nanospike-covered Ni foam-based catalyst showed a performance similar to that of synthetic urea, offering its industrial value. Other intuition of selecting [MoS4]2- was to provide a ligand-based mechanism for hydrogen evolution half-cell [hydrogen evolution reaction (HER)] to preclude the HER-competing oxygen reduction. Another crucial point of our work is its potential to avoid the mixing of two explosive product gases, that is, H2 and O-2.
Keywords: hydrogen evolution reaction; Layered double hydroxide; nickel oxyhydroxide; sewage denitrification; urea oxidation reaction; urine/urea electrolysis